Prevalent human papillomavirus infection increases the risk of HIV acquisition in African women: advancing the argument for human papillomavirus immunization. (1st February 2022) - Liu, Gui; Mugo, Nelly R.; Brown, Elizabeth R.; Mgodi, Nyaradzo M.; Chirenje, Zvavahera M.; Marrazzo, Jeanne M.; Winer, Rachel L.; Mansoor, Leila; Palanee-Phillips, Thesla; Siva, Samantha S.; Naidoo, Logashvari; Jeenarain, Nitesha; et al.
Abstract : Objective: Vaccine-preventable human papillomavirus (HPV) infection is common, especially in sub-Saharan Africa where HIV risk is also high. However, unlike other sexually transmitted infections (STIs), HPV's role in HIV acquisition is unclear. We evaluated this relationship using data from MTN-003, a clinical trial of HIV chemoprophylaxis among cisgender women in sub-Saharan Africa. Design: A case–control study. Methods: We matched 138 women who acquired HIV (cases) to 412 HIV-negative controls. Cervicovaginal swabs collected within 6 months before HIV seroconversion were tested for HPV DNA. We estimated the associations between carcinogenic (high-risk) and low-risk HPV types and types targeted by HPV vaccines and HIV acquisition, using conditional logistic regression models adjusted for time-varying sexual behaviors and other STIs. Results: Mean age was 23 (±4) years. Any, high-risk and low-risk HPV was detected in 84, 74 and 66% of cases, and 65, 55 and 48% of controls. Infection with at least two HPV types was common in cases (67%) and controls (49%), as was infection with nonavalent vaccine-targeted types (60 and 42%). HIV acquisition increased with any [adjusted odds ratio (aOR) 2.5, 95% confidence interval (95% CI) 1.3–4.7], high-risk (aOR 2.6, 95% CI 1.5–4.6) and low-risk (aOR 1.8, 95% CI 1.1–2.9) HPV. Each additional type detected increased HIV risk by 20% (aOR 1.2, 95% CI 1.1–1.4). HIV acquisition was associated with HPV types targeted by the nonavalent (aOR 2.1, 95% CI 1.3–3.6) and quadrivalent vaccines (aOR 1.9, 95% CI 1.1–3.2). Conclusion: HPV infection is associated with HIV acquisition in sub-Saharan African women. In addition to preventing HPV-associated cancers, increasing HPV vaccination coverage could potentially reduce HIV incidence.